What’s Love Got to Do with It?: Ultranationalism, Islamophobia, and Hate Crime in Sweden - Gardell, Mattias (Journal of religion and violence, 2015)
Sweden is known for its tolerance and liberal policies. Yet, sixty percent of Sweden’s mosques and Islamic centres had been subjected to threats, vandalism, or arson. Muslim women, in particular, seem to be targets of hate crimes, but rarely report incidents to the police. In 2014, the Sweden Democrats, a proto-fascist nationalist party, gained close to 13 percent of the national vote after a fervent anti-Muslim campaign supported by a network of social media outlets in which incitements to violence against Muslim-Swedes proliferated. Based on fieldwork, surveys, and open-ended interviews with 100 Muslim citizens and 40 anti-Muslim activist, as well as a review of anti-Muslim online calls to arms, this essay addresses the surge of anti-Muslim hate crime in Sweden, exploring the role of violence in the proto-fascist attempt to ‘recreate’ a homogenous nation that never existed. While the literature on ultranationalist-inspired hate crime typically sees the perpetrators as angry white men, the nationalists interviewed in this study claimed to act out of love, not hate. By examining how love and hate may reinforce each other, this essay argues that anti-Muslim hate crime is a form of political violence that patrols the borders and identities it produces, and shows the extent to which victims may adopt the perpetrator’s gaze and experience their own bodies as deviant, and out of place in their own home country.